Optimal revenue sharing model of a wind–solar-storage hybrid energy plant under the green power trading market - Zeng, Zhuo; Gao, Xiang; Fang, Baling; Zhang, Tao; Zhu, Ying (Frontiers in Energy Research, 2024)
This paper proposes an optimal revenue sharing model of wind-solar-storage hybrid energy plant under medium and long-term green power trading market to facilitate the coordinated operation and equitable revenue allocation. Firstly, a method for decomposing transaction volume of green power is introduced by considering the uncertainty of spot market prices and physical delivery characteristics of green power trading. Then, a coordinated scheduling strategy of hybrid renewable energy plant is proposed to maximize revenues generated from both the green power and spot markets. Consequently, a costbenefit contribution index system is developed to quantify the contribution of energy storage in the wind-solar-storage hybrid power plant. A cooperation revenue sharing model with contribution degree correction based on the minimum cost-remaining savings (MCRS) method is also proposed. The superiority of the proposed cooperation revenue sharing model for profitability enhancement of energy storage is validated through comparative case studies.